Vascular adhesion protein-1 is elevated in primary sclerosing cholangitis, is predictive of clinical outcome and facilitates recruitment of gut-tropic lymphocytes to liver in a substrate-dependent manner. Issue 6 (20th April 2017) - Trivedi, Palak J; Tickle, Joseph; Vesterhus, Mette Nåmdal; Eddowes, Peter J; Bruns, Tony; Vainio, Jani; Parker, Richard; Smith, David; Liaskou, Evaggelia; Thorbjørnsen, Liv Wenche; Hirschfield, Gideon M; Auvinen, Kaisa; et al.
Abstract : Objective: Primary sclerosing cholangitis (PSC) is the classical hepatobiliary manifestation of IBD. This clinical association is linked pathologically to the recruitment of mucosal T cells to the liver, via vascular adhesion protein (VAP)-1-dependent enzyme activity. Our aim was to examine the expression, function and enzymatic activation of the ectoenzyme VAP-1 in patients with PSC. Design: We examined VAP-1 expression in patients with PSC, correlated levels with clinical characteristics and determined the functional consequences of enzyme activation by specific enzyme substrates on hepatic endothelium. Results: The intrahepatic enzyme activity of VAP-1 was elevated in PSC versus immune-mediated disease controls and non-diseased liver (p<0.001). The adhesion of gut-tropic α4β7 + lymphocytes to hepatic endothelial cells in vitro under flow was attenuated by 50% following administration of the VAP-1 inhibitor semicarbazide (p<0.01). Of a number of natural VAP-1 substrates tested, cysteamine—which can be secreted by inflamed colonic epithelium and gut bacteria—was the most efficient (yielded the highest enzymatic rate) and efficacious in its ability to induce expression of functional mucosal addressin cell adhesion molecule-1 on hepatic endothelium. In a prospectively evaluated patient cohort with PSC, elevated serum soluble (s)VAP-1 levels predicted poorer transplant-free survival for patients, independently (HR: 3.85, p=0.003) and additively (HR: 2.02, p=0.012) of the presence of liver cirrhosis. Conclusions: VAP-1 expression is increased in PSC, facilitates adhesion of gut-tropic lymphocytes to liver endothelium in a substrate-dependent manner, and elevated levels of its circulating form predict clinical outcome in patients.